2023
DOI: 10.1111/bjh.18872
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to vincristine in DLBCL by disruption of p53‐induced cell cycle arrest and apoptosis mediated by KIF18B and USP28

Abstract: SummaryThe frontline therapy R‐CHOP for patients with diffuse large B‐cell lymphoma (DLBCL) has remained unchanged for two decades despite numerous Phase III clinical trials investigating new alternatives. Multiple large studies have uncovered genetic subtypes of DLBCL enabling a targeted approach. To further pave the way for precision oncology, we perform genome‐wide CRISPR screening to uncover the cellular response to one of the components of R‐CHOP, vincristine, in the DLBCL cell line SU‐DHL‐5. We discover … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 65 publications
(136 reference statements)
0
2
0
Order By: Relevance
“…In this issue, Rovsing et al 9 performed a genome-wide CRISPR screen in the germinal centre B-cell-like (GCB)-DLBCL cell line SU-DHL-5 to investigate the cellular…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue, Rovsing et al 9 performed a genome-wide CRISPR screen in the germinal centre B-cell-like (GCB)-DLBCL cell line SU-DHL-5 to investigate the cellular…”
mentioning
confidence: 99%
“…In this issue, Rovsing et al 9 performed a genome‐wide CRISPR screen in the germinal centre B‐cell‐like (GCB)‐DLBCL cell line SU‐DHL‐5 to investigate the cellular response to vincristine. They identified genes related to mitotic spindle organization that are essential during vincristine treatment and found that the inhibition of the kinesin‐8 motor family member KIF18A using a small‐molecule inhibitor BTB‐1, in combination with vincristine, caused complete cell death synergistically in SU‐DHL‐5 and another GCB‐DLBCL cell line OCI‐Ly7.…”
mentioning
confidence: 99%